Android-Based Information System for Monitoring and Evaluation of Industrial Internship Activities - Ardhiansyah Wahyu Setyadi; Rodhiyah Mardhiyyah (Kirana Publisher (KNPub), 2025)
Industrial work practice is a compulsory program for vocational high school students as part of work-based learning. In Temanggung, monitoring and evaluation are still done manually using paper documents, making it difficult for teachers and industry supervisors to track students’ progress in real time. The separation of attendance, activity reports, and performance assessments also causes inefficiency and potential data loss. To address this, an Android-based information system was developed to provide real-time monitoring and integrate all evaluation components into one platform. Students, teachers, and industry partners use the mobile app, while administrators manage data through a web-based system. The system enables supervisors to monitor students’ daily activities remotely and unifies attendance, reports, and performance assessments in a single platform, improving administrative efficiency and simplifying the management of industrial work practice activities at SMK N 2 Temanggung.